Attachment insecurity, heart rate variability, and perceived social support in a diverse sample of young adults - Pourmand, Vida; Froidevaux, Nicole M.; Williams, DeWayne P.; Yim, Ilona S.; Campos, Belinda (Frontiers in Psychology, 2023)
Psychological and physical factors are robustly associated with perceived social support.Drawing from the literature on attachment style in adults and psychophysiology, we examined the possibility that the interaction of attachment insecurity and resting heart rate variability (HRV) was associated with perceived social support in a diverse sample of young adults living in the U.S (N = 145, Mage = 20.45) that was majority Latino (n = 77). Analyses revealed three key findings. First, in the overall sample, attachment avoidance and attachment anxiety were negatively associated with perceived social support, but in the Latino sample, only attachment avoidance was negatively associated with perceived social support. Second, HRV was not associated with perceived social support in the overall sample nor in the Latino sample. Third, attachment insecurity and HRV interacted to predict perceived social support only in the Latino sample such that, for those with lower levels of HRV, attachment anxiety was positively associated with perceived social support. This study underscores the importance of examining both psychological and physiological processes with careful consideration of ethnicity/culture in order to better understand perceived social support.